Islamic actors' support for democracy and European integration: A case for power-seeking? - Arolda Elbasani; Beken Saatçioğlu (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2011)
This paper investigates when and how Islamic political actors support democracy, and in particular, the EU's democratic criteria subsumed under membership conditionality. The research focuses on the main Islamic organizations in two Muslim-majority, EU applicant states, Turkey and Albania. The analysis suggests that Islamic actors endorsed democratic rules based on a rationalist logic, which combines interest-driven and ideational concerns. The weak Albanian actors have shown unconditional support for democracy and related EU-demanded reforms, which ultimately improved their fragile domestic power position. In contrast, Turkey's considerably stronger, Islamic-rooted Justice and Development Party supported democracy and EU conditions more selectively, and so long as it needed the empowerment associated with democratic and EU rules. These findings highlight the strong relationship between Islamic actors' political power considerations and support for democracy.
Keywords: 320; Islam; European integration; Turkey; Albania; power-seeking